2023
DOI: 10.1021/acs.analchem.3c01251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Repair Enzyme Fluorescent Probe to Reveal the Intracellular DNA Damage Induced by Benzo[a]pyrene in Living Cells

Abstract: Pollutant exposure causes a series of DNA damage in cells, resulting in the initiation and progression of diseases and even cancers. An investigation of the DNA damage induced by pollutants in living cells is significant to evaluate the cytotoxicity, genotoxicity, and carcinogenicity of environmental exposure, providing critical insight in the exploration of the etiologies of diseases. In this study, we develop a repair enzyme fluorescent probe to reveal the DNA damage caused by an environmental pollutant in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The study employed a mouse model induced with benzo­( a )­pyrene compounds (BAP) to assess further the therapeutic effectiveness of developing cancer. BAP, a polycyclic aromatic hydrocarbon (PAH), is known for its exceptionally high carcinogenic potential. , This propensity arises from the metabolic conversion of PAH compounds in the body into diol epoxides, , which subsequently bind to DNA and initiate the carcinogenic process. The results demonstrated that the B-CDs/Naproxen group exhibited a significant decrease in malignancy diameter throughout the study, while the control group showed a notable increase in cancer size volume.…”
Section: Discussionmentioning
confidence: 99%
“…The study employed a mouse model induced with benzo­( a )­pyrene compounds (BAP) to assess further the therapeutic effectiveness of developing cancer. BAP, a polycyclic aromatic hydrocarbon (PAH), is known for its exceptionally high carcinogenic potential. , This propensity arises from the metabolic conversion of PAH compounds in the body into diol epoxides, , which subsequently bind to DNA and initiate the carcinogenic process. The results demonstrated that the B-CDs/Naproxen group exhibited a significant decrease in malignancy diameter throughout the study, while the control group showed a notable increase in cancer size volume.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recognition efficiency was constrained by the limited local concentration of the AP site on DNA hairpin recognizers. Researchers found that improving the local concentration of hairpins was a very effective approach for boosting reaction kinetics. , For example, Deng’s group developed the spherical nucleic acids by attaching AP site modified DNA hairpins on the surface of the ZnO 2 nanoparticles, allowing for highly sensitive and selective detection of APE1 . However, the DNA hairpins assembled on the ZnO 2 surface were disordered and time-consuming, making it difficult to avoid invalid collisions and steric hindrance .…”
Section: Introductionmentioning
confidence: 99%